2016
DOI: 10.18685/ejbme(7)1_ejbme-15-013
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between job stress and organizational commitment: An empirical study of banking sector

Abstract: Stress can be defined as experienced discrepancy between demand of environment and capabilities of individual. In every phase of life, every individual has to face stress. Employees in different organizations face stress. Especially in the banking sector, employees face great stress due to many stress antecedents like lack of support from supervisors, great pressure of work, problematic co-workers relationship and family and work life conflicts. All these stressors lead to low organizational commitment and abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 2 publications
3
26
1
9
Order By: Relevance
“…Arogundade and Onabanjo (2013)observed that stress is a term that is widely used in everyday life and it is globally acknowledged as a major challenge to workers' health and the health of an organization. Bhatti, Bhatti, Akram, Hashim, Akram, and Akram (2016) defined job stress as the harmful physical and emotional responses that happen when the requirements of the job do not match the competences, resources, or needs of the worker. Similarly, job stress may be conceptualized as a situation where employees' skills knowledge and abilities do not match with organizational requirements (Bhatti et al 2016).Occupational stress has a negative effect on a person's psychological and physical health as well as an organization's effectiveness (Divakar,2015).…”
Section: Scope Of the Studymentioning
confidence: 99%
“…Arogundade and Onabanjo (2013)observed that stress is a term that is widely used in everyday life and it is globally acknowledged as a major challenge to workers' health and the health of an organization. Bhatti, Bhatti, Akram, Hashim, Akram, and Akram (2016) defined job stress as the harmful physical and emotional responses that happen when the requirements of the job do not match the competences, resources, or needs of the worker. Similarly, job stress may be conceptualized as a situation where employees' skills knowledge and abilities do not match with organizational requirements (Bhatti et al 2016).Occupational stress has a negative effect on a person's psychological and physical health as well as an organization's effectiveness (Divakar,2015).…”
Section: Scope Of the Studymentioning
confidence: 99%
“…In addition, another result of our research is that there is a negative correlation between job-related stress and emotional, normative, and overall organizational commitment. Looking at studies in foreign literature, many studies show that job-related stress has a significant and negative correlation with an organizational commitment [28][29][30][31][32][33][34][35]. The results of the research examining the characteristics between organizational commitment and job-related stress of nurses who play an active role in achieving the goals and objectives of hospitals and providing a quality and efficient service also support the results of our study [15,25,29,32,[36][37][38][39][40][41][42][43][44].…”
Section: Correlation Analysis Table 2 Correlation Analysis Between Organizational Commitment and Job-related Tension Scoresmentioning
confidence: 99%
“…Bireysel anlamda; fizyolojik hastalıklara (baş ağrısı, uyku bozukluğu), psikolojik rahatsızlıklara (endişe, depresyon, öfke, unutkanlık, çaresizlik hissi) ve davranışsal bozukluklara (alkol, sigara, uyku hapı kullanımı, saldırgan davranışlar, iş kazaları) neden olmaktadır (Gillespie, Walsh, Winefield, Dua ve Stough, 2001, s.65-66;Ross ve Altmaier, 1994, s. 12-13). Diğer taraftan, iş stresinin örgütsel çıktılarla ilişkisini inceleyen çalışmalarda, iş stresinin iş tatmini (O'Neill ve Davis, 2011), performans (Irawanto, Noermiyati ve Primasari, 2015) ve örgüte bağlılığı (Bhatti, Bhatti, Akram, Hashim ve Akram, 2016) azalttığı; tükenmişlik (Khattak, Khan, Haq, Arif ve Minhas, 2011) ve devamsızlığı (Vasse, Nijhuis ve Kok, 1998) arttırdığı tespit edilmiştir.…”
Section: İş Stresiunclassified